Collective and state violence in Turkey (New York ; Oxford)
xi, 578 sayfa
Keywords: “Turkey has gone through significant transformations over the last century-from the Ottoman Empire and Young Turk era to the Republic of today-but throughout it has demonstrated troubling continuities in its encouragement and deployment of mass violence. In particular, the construction of a Muslim-Turkish identity has been achieved in part by designating “internal enemies“ at whom public hatred can be directed. This volume provides a wide range of case studies and historiographical reflections on the alarming recurrence of such violence in Turkish history, as atrocities against varied ethnic-religious groups from the nineteenth century to today have propelled the nation's very sense of itself.“ --